Cathodoluminescence and Photoconductive Characteristics of Single‐Crystal Ternary CdS/CdSe/CdS Biaxial Nanobelts. Issue 13 (10th November 2014) - Hu, Linfeng; Yan, Jian; Kim, Yong; Fei, Guangtao; Watanabe, Kentaro; Sekiguchi, Takashi; Zhang, Lide; Fang, Xiaosheng
<x xml:space="preserve">Abstract</x> The cathodoluminescence and optoelectronic properties based on an individual CdS/CdSe/CdS biaxial nanobelt are revealed in the present study. Both typical CdS and CdSe emissions are detected from as‐grown CdS/CdSe/CdS nanobelts. The photodetector based on this nanobelt exhibits high sensitivity and excellent cycle stability. This opens a door to rational design of germanium chalcogenide compounds with unique optical properties. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>